Recurso estilísticos en la producción narrativa de las novelas Bartleby y compañía y El mal de Montano de Enrique Vila-Matas - Gutiérrez Muñoz, Óscar (Acta Hispanica, 2015)
In this paper we attempt to analyzethe stylistic resources used by the Spanishwriter Enrique Vila-Matas in the constructionof his novels Bartleby & Co., and El mal deMontano. We focus on the use of certain aspectsof intertextual mechanisms, displayed in thedevelopment of the fable, which gave rise tothese novels. Thus, we reflect on the constructionof the characters, as well as on theirrelationship to both the archive and literarytradition.